Prediction of concentration levels of metformin and other high consumption pharmaceuticals in wastewater and regional surface water based on sales data - Oosterhuis, Mathijs; Sacher, Frank; ter Laak, Thomas L. (The Science of the total environment, 2013)
Local consumption data of pharmaceuticals were used to study the emission to wastewater and surface waters in two small Dutch water catchments. For nine high consumption pharmaceuticals: metformin, metoprolol, sotalol, losartan, valsartan, irbesartan, hydrochlorothiazide, diclofenac and carbamazepine, predicted emissions were compared to wastewater concentrations, removal in sewage treatment plants and recovery in regional surface water. The study shows that local consumption data can be very useful to select pharmaceuticals for monitoring and to predict wastewater concentrations. Measured influent concentrations were on average 78% with a range of 31–138% of predicted influent concentrations. Metformin is the pharmaceutical with the highest concentration in wastewater (64–98μg/L) but it is removed with >98% in sewage treatment plants (STP). Guanylurea, a biodegradation product of metformin, was detected in STP effluents and surface waters at concentrations of 39–56μg/L and 1.8–3.9μg/L, respectively. The STP removal of the different pharmaceuticals varied strongly. For carbamazepine, hydrochlorothiazide and sotalol a significant better removal was found at higher temperatures and longer hydraulic retention times while for metoprolol significantly better removal was only observed at higher temperatures. Predicting environmental concentrations from regional consumption data might be an alternative to monitoring of pharmaceuticals in wastewater and surface waters. ► Regional sales relevant for monitoring and emission prediction of pharmaceuticals ► Metformin concentrations are 80μg/L and 1μg/L in wastewater and effluent respectively. ► 82% of metformin in wastewater recovered as guanylurea in effluent. ► Significant better removal at higher temperatures for 4 of 9 pharmaceuticals ► Significant better removal at higher HRTs for 3 of 9 pharmaceuticals